Breast cancer in reproductive-age women: oncofertility perspectives, treatment impact, and fertility preservation strategies - Chadha, Saloni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Breast cancer remains the most prevalent malignancy among females globally, comprising 12.5% of all cancer cases. While the median age of diagnosis in Western populations is 62 years, India reports a significantly younger median age of approximately 49 years, correlating with its youthful demographic profile. The incidence of breast cancer in women of reproductive age- approximately 19.3 per 100,000- has been rising steadily, necessitating urgent attention to fertility preservation in this population. Cancer treatments such as gonadotoxic chemotherapy, endocrine therapy, and radiation can adversely affect ovarian reserve, delay childbearing, or induce premature ovarian insufficiency. Consequently, fertility preservation has emerged as a crucial component of cancer care for young survivors. Oncofertility, an evolving interdisciplinary field, integrates oncology and reproductive medicine to provide comprehensive fertility counselling and interventions for cancer patients. Despite the growing importance of fertility preservation, barriers such as inadequate referral, limited awareness, financial constraints, and concerns regarding delays in cancer treatment or hormonal stimulation in hormone-positive cases hinder access. The impact of treatment on fertility varies depending on age, ovarian reserve, and treatment modality. Options for fertility preservation include embryo cryopreservation, mature and immature oocyte freezing, ovarian tissue cryopreservation, and temporary ovarian suppression using GnRH agonists. The National Comprehensive Cancer Network (NCCN) recommends early fertility discussions for all premenopausal breast cancer patients. In addition, pregnancy-associated breast cancer (PABC), though rare, presents a clinical challenge due to diagnostic delays and treatment limitations during gestation. As survival rates improve, safeguarding reproductive potential becomes vital to the quality of life of young survivors. Individualized, timely fertility preservation strategies supported by national and international guidelines are key to improving outcomes in reproductive-age women with breast cancer.